Nodding syndrome since 2012: recent progress, challenges and recommendations for future research. Issue 2 (19th November 2014) - Colebunders, R.; Post, R.; O'Neill, S.; Haesaert, G.; Opar, B.; Lakwo, T.; Laudisoit, A.; Hendy, A.
Abstract We aim to review the current epidemiology of nodding syndrome (NS) and discuss relevant gaps in research. NS and convulsive epilepsy of unknown aetiology are clustered within the same villages and families in onchocerciasis‐endemic areas. They are therefore potentially different clinical expressions of the same disease. It has been difficult to perform full autopsies on NS patients who die in remote villages. Adequate fixation of tissue immediately after death is critical for the examination of brain tissue. Therefore, post‐mortem transsphenoidal brain biopsies, performed immediately after death by trained nurses, will provide the best option for obtaining tissue for analysis. We suspect that certain blackflies in onchocerciasis‐endemic areas may transmit a novel pathogen that could cause NS and epilepsy. This is supported by a recent drop in the number of new NS cases coinciding with vector control activities aimed at reducing blackfly populations in northern Uganda. We propose that metagenomic studies of human samples, blackflies and microfilariae are conducted to screen for pathogens, and that a clinical trial is planned to evaluate the impact of larviciding against NS and epilepsy epidemics.